Implementasi Pendidikan Karakter Religius Dalam Menghadapi Era Globalisasi Pada Pondok Pesantren Habiburrahman - Giantomi Muhammad; Andewi Suhartini; Nurwadjah Ahmad (Ulumuddin : Jurnal Ilmu-ilmu Keislaman, 2022)
Pesantren is the oldest educational institution in Indonesia and has made a major contribution to the nation and religion in Indonesia in addition to providing the implementation of quality education and teaching by emphasizing spiritual values, it has also given birth to alumni who have religious intellectuality and are ready to become leaders of the nation, especially for Muslims. . Reflected in the Habiburrahman Islamic Boarding School which emphasizes the formation of religious character to its students in facing the era of globalization that is currently happening. The students are demanded to have a personality with strong religious character and can make the era of globalization a challenge and opportunity in integrating Islamic values. The application of education and teaching at the Habiburrahman Islamic Boarding School is characterized by strengthening the character of students to form a strong personality of faith and piety and can form a person who has good morals in the midst of globalization and is ready to enter the community as a leader who often preaches in enforcing amar ma'ruf nahi munkar.